Students’ views on audio visual aids used during didactic lectures in a medical college - Kumar, Ashutosh; Singh, Ramanuj; Mohan, Lalit; Kumar, Mani Kant (Asian Journal of Medical Sciences, 2013)
Introduction: Medical teachers have conventionally been using different teaching methods to educate medical students previously dominated by blackboard and slide projectors. Now day’s audiovisual aids such as power point have been used. The optimum use of audiovisual aids is essential forderiving their benefits. This study was done to know the students’ preference regarding the various audiovisual aids, with an aim to improve their use in didactic lectures. Material &Methods: Two hundred and eighty six from first, second and third professional medical students were invited to participate in a questionnaire based study. Two hundred and thirteen (74.4%) students completed the questionnaire and their responses were analyzed. The first part of the questionnaire included demographic and educational details. The second part consisted of 12 statements regarding the preference of audiovisual aids for various aspects of learning. Results: In this study, 90.1% of the respondents (first, second & third professional) were stimulated for further reading if they attended a lecture which was augmented by the use of visual aids. The respondents preferred a combination of audiovisual aids during a didactic lecture. The perception of diagrams, flow charts and note taking was best accepted with a power point presentation by first and second professional students, whereas OHP preferred by third professional students . In understanding a particular topic, a combination of aids scored over the use of a particular visual aid alone. In listening and understanding a particular topic, power point presentation was the most preferred aid, with the blackboard being preferred by third professional students. About 62.4% of the respondents were interested in taking notes during class compare to handouts. Conclusion: Our study demonstrates that lectures delivered by using a combination of audio visual aids are more appreciated by the students. Furthermore, the lecture should be constructed in a fashion so as to enable the students to gather factual information easily and in a concise manner. Teachers should note that the students preferred a combination of visual aids and were interested in taking notes during lectures. DOI: http://dx.doi.org/10.3126/ajms.v4i2.8031 Asian Journal of Medical Sciences 4(2013) 36-40